Contribuições para a modernização administrativa das secretarias de pós-graduação da UFSM - Rachele, Rone Maria (2023)
The goal of this research is to provide improvements to standardization of the UFSM Integrated Postgraduate Secretariats’ processes. The way in which institutions are organized and managed has a direct impact on their results. In this way, managers must practice actions that seek more efficient management. It is important to discuss new organizational models and to review work processes. This study involved documentary and bibliographical research, interviews with the actors involved in the processes and participation of the researcher in meetings to discuss the processes of an Integrated Secretariat of UFSM. Later, mapping of processes using the Bizagi software, proposition of improvements and preparation of an Integrated Secretariat Process Manual were delineated. A manual that may be suitable for UFSM Units that have not yet undergone a restructuring process was compileted. In addition, it can serve as a subsidy for the implementation of processes that are not yet taking place by the PEN SIE. The analysis of the mapped processes can also contribute to the optimization and other studies aimed at implementing the culture of management by processes at UFSM and consequent administrative modernization.